Meningkatkan Pendapatan Petani melalui Pendampingan Budidaya Pisang Cavendish di Desa Sukadana - Zuhdiyah Matienatul Iemaaniah; Dori Kusuma Jaya; Siska Ita Selvia; Suprayanti Martia Dewi; Afifah Farida Jufri; Dwi Noorma Putri; Novita Hidayatun Nuvus; Anjar Pranggawan Azhari; Amrul Jihadi; Yuliana Asri (Politeknik Piksi Ganesha Indonesia, 2024)
The development of cavendish banana cultivation has higher potential compared to other types of bananas. This is because Cavendish bananas have a higher market selling value, especially as they are a type of banana that sells well on the international market. One of the villages that has the potential to develop cavendish banana tree cultivation is Sukadana Village. This village is one of the buffer villages for the Mandalika Special Economic Zone which is expected to provide basic agricultural needs in the Mandalika area. Service activities will be carried out in December 2022 until may 2023 with the target farmer group Patuh Bersama. This service activity aims to increase community income through assistance in the cultivation of Cavendish bananas. The results of the service activities carried out are providing insight to the community that cavedish bananas are a type of banana that is commonly consumed by the international community. Apart from that, the community can also develop the cultivation of cavendish bananas not only in their yards, but can also cultivate them on unused agricultural land